Božena Viková-Kunětická and Fascism: Between Reason and Strife (Theatrum historiae, 2025)
This study explores Božena Viková-Kunětická’s relationship with inter-war fascism. Starting out from an analysis of her journalism and speeches, it traces this relationship on two levels. On the first it reconstructs Viková-Kunětická’s sympathies with fascism as a new political phenomenon and her relationship with the emerging proto-fascist and fascist organisations in Czechoslovakia. In the second section it seeks an answer to the question concerning the extent to which elements of fascist ideology are present in her thought and rhetoric – specifically populist ultranationalism and the myth of palingenesis. The conclusion then focuses on an interpretation of the causes of her partial inclination towards fascism.
Keywords: Božena Viková-Kunětická; Fascism; Nationalism; Czechoslovak National Democracy; First Czechoslovak Republic